Ikeda Kotaro y Uchida Naosaku (Eds.), Social and economic aspects of Japan. Seijo Gakuen jubilee year, 1917-1967. Tokyo, Economic Institute of Seijo University, 1967. 263 pp. - Tanaka de Saldívar, Michiko (Estudios de Asia y África, 1969)
-